The Effectiveness of English Learning with the Blended Learning Method in the Digital Era: A Literature Review - Yuanita Susanti; Afif Alfiyanto; Fitri Hidayati; Muhammad Ghazali (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to explore the effectiveness of United Kingdom language learning with blended learning methods in the digital era. The blended learning method combines face-to-face learning with online learning, which allows flexibility in time and place for students. This study uses a descriptive literature review approach by reviewing relevant articles and journals in the last 10 years (2013-2023) related to the application of blended learning in United Kingdom learning. The results of the study show that the blended learning method is effective in improving students' United Kingdom language skills, especially in speaking and listening skills. Flexibility and the use of interactive technology are the main factors that support the success of this method. However, the study also identified several challenges, such as limited access to technology and low digital literacy, that hinder the implementation of blended learning, especially in developing countries. The novelty of this study lies in a more in-depth analysis of local challenges in the application of blended learning and solutions to improve its effectiveness. This research emphasizes the importance of the role of adequate technology infrastructure and digital literacy training to support the successful implementation of blended learning in the future.